2016
DOI: 10.1080/03079457.2015.1110850
|View full text |Cite
|
Sign up to set email alerts
|

Protection provided by Rispens CVI988 vaccine against Marek's disease virus isolates of different pathotypes and early prediction of vaccine take and MD outcome

Abstract: We tested the level of protection provided by the Rispens CVI988 (Rispens) vaccine against challenge with a virulent Marek's disease virus (MDV) pathotype (vMDV) and a very virulent pathotype (vvMDV) and the accuracy of a range of predictive measures of Marek's disease (MD) incidence and vaccine take. Commercial layer chicks (n = 236) were vaccinated (or not) with 4000 plaque-forming units (pfu) of Rispens vaccine at hatch and challenged (or not) with 500 pfu of each challenge virus five days post vaccination.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Sporadic epidemics of MD have been reported worldwide, even in vaccinated flocks [ 16 ], indicating that the virulence of MDV has increased in recent decades, and some of the more recent isolates are more pathogenic to chickens than older isolates [ 17 , 18 ]. Thus, the increased use of vaccines has led the virus to evolve toward higher virulence, which can overcome the protection conferred by currently available vaccines [ 19 ]. It has been suggested that the widespread use of the CVI988 vaccine strain may have led to the emergence of new, more virulent pathotypes [ 20 ], and there are serious concerns that such pathotypes are circulating in Tunisia, especially due to the excessive use of vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…Sporadic epidemics of MD have been reported worldwide, even in vaccinated flocks [ 16 ], indicating that the virulence of MDV has increased in recent decades, and some of the more recent isolates are more pathogenic to chickens than older isolates [ 17 , 18 ]. Thus, the increased use of vaccines has led the virus to evolve toward higher virulence, which can overcome the protection conferred by currently available vaccines [ 19 ]. It has been suggested that the widespread use of the CVI988 vaccine strain may have led to the emergence of new, more virulent pathotypes [ 20 ], and there are serious concerns that such pathotypes are circulating in Tunisia, especially due to the excessive use of vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…All model parameters were extracted from available data (Atkins et al, 2013a, 2011a; Cui et al, 2016; Kennedy et al, 2018; Ralapanawe et al, 2016b, 2016a; Zhang et al, 2015). Parameters associated to barn characteristics where obtained from communication with Burnbrae Farms in Ontario Canada, or the literature.…”
Section: Methodsmentioning
confidence: 99%
“…We assume dust shed by MDV infected laying-hens contain viral particles proportional to the virulence level of the MDV strain (Ralapanawe et al, 2016a). To obtain the viral shedding rate, we took Atkins et al (2011) model of daily dander shedding for a typical broiler bird and arameterized it according to a recent study on dust shed from MDV infected layer chickens vaccinated with Rispen CVI988 (Atkins et al, 2011a; Ralapanawe et al, 2016b, 2016a). Thereby, we obtain the viral shedding rates κ for each MDV strain from data on the dust shed from a typical laying-hen (Table S4), and the viral copy number (VCN) of MDV per milligram of dust for vMDV (pathotype MPF57) and vvMDV (pathotype FT158) (Table S3), and over each cohort duration (older chickens will shed more viral particles) (Table S5) (Bell, 2003; Witter et al, 1968).…”
Section: Methodsmentioning
confidence: 99%
“…MDV was the only poultry live vaccine whose vaccination uptake efficacy was studied by demonstrating its presence in feather tips. The presence of live vaccines was demonstrated in the feathers of experimentally infected and commercially vaccinated layers in Australia [23][24][25]. By developing a novel nested real-time PCR assay we were able to characterize the vaccine application efficacy in commercially vaccinated chicks in Israel [13] and to trace back MDV-affected chicken flocks to problematic MDV vaccine application [14].…”
Section: Feathers As the Main Site Of Marek's Disease Virus (Mdv) Repmentioning
confidence: 99%